Estudio de la hidratación de cementos de fosfato tricálcico - Medina., N.; Rodríguez., H.; Piña., C. (Revista Mexicana de Ingenieria Biomedica, 2009)
The reaction kinetics, the microstructure and transformation mechanism of reagents of three biocementos based on α-tricalcium phosphate (TCP-α), seeds hydroxyapatite (HA) and zirconium oxide (ZrO2), were studied. It was found that the use of additives enriched with Ca or P, with higher solubility than the solubility of the reactive, it favors the sobresaturation of the liquid phase, which precipitates in CDHA or HA. The CaCl2 and NaH2PO act as important sources of Ca2+ and PO43- , it was found that the used concentrations in liquid phase convert completely α-TCP in HA in hours, also that the crystallinity is higher employing salts NaH2PO4 than Na2HPO4. They have the advantage over cement of methyl methacrylate, that are usually used, that they react below 40°C while the MMA reach it near to 100 °C damaging the surrounding tissue. In addition, these biocements are bioactive and bioabsorbable. They are proposed for the repair and bone fixation implants and/or prosthetics.